Contrasting geomorphological storm response from two adjacent shorefaces. Issue 15 (7th October 2015) - Backstrom, Joni; Jackson, Derek; Cooper, Andrew; Loureiro, Carlos
Abstract: Shorefaces play a critical role in cross‐shore sediment transport between the beach and inner shelf, particularly during storm conditions. A comparison and examination of storm‐driven sedimentary changes on two adjacent shorefaces in Northern Ireland, located only 5 km apart, revealed significantly different geomorphological responses. The steeper shoreface at West Strand responded with extensive sediment deposition across almost the entire shoreface, in contrast with the more dissipative and quasi‐linear shoreface at Portstewart, which mostly showed nearshore bar changes. Results from the two sites, which have similar wave/wind characteristics and seabed sediments, suggest that: (i) cross‐shore morphology, (ii) immediately previous (antecedent) shoreface morphodynamic behaviour and (iii) the presence, or lack of, offshore sand appear to be the primary controls on storm‐driven sedimentary changes attributed to the high‐energy event. Copyright © 2015 John Wiley & Sons, Ltd.